The Role of Sharia Financial Technology (Fintech) in Increasing MSME’s Financial Access - Andi Zakaria (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
The development of Sharia-based financial technology (Fintech) has significantly improved financial access for Micro, Small, and Medium Enterprises (UMKM) in Indonesia. Many UMKM struggle to secure funding from conventional financial institutions due to collateral and administrative constraints. Sharia Fintech provides an alternative through Sharia-compliant financing models such as peer-to-peer (P2P) lending, crowdfunding, and profit-sharing schemes (mudharabah and musyarakah). This study analyzes the role of Sharia Fintech in expanding UMKM financing using a qualitative descriptive method with a case study approach on several Sharia Fintech platforms in Indonesia. Data was collected through interviews with MSME actors, document analysis, and literature reviews, then analyzed using triangulation for validity. The findings reveal that Sharia Fintech enhances financial accessibility through ease of access, fast fund disbursement, and a flexible financing system. However, challenges remain, including low Sharia financial literacy, regulatory limitations, and digital adoption barriers. Strengthening regulations, enhancing financial education, and optimizing technology use are essential to improving Sharia Fintech’s effectiveness as an inclusive and sustainable MSME financing instrument.